Pengaruh Variasi Dosis Pakan Konsentrat Terhadap Pertumbuhan Bobot Badan Ayam Broiler - Ulfahtun Hasanah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
This study aimed to determine the effect of varying concentrate feed dosages on broiler chicken body weight growth. Broiler chickens are a poultry commodity with a rapid growth rate that is greatly influenced by the quality and quantity of feed provided. The research method used was an experiment with several different concentrate feed dosage treatments: 30%, 40%, 50%, and 60% of the total daily ration. Each treatment was carried out on groups of broiler chickens with uniform numbers and initial conditions, and maintained during a specific growth period. The parameters observed were weekly body weight gain and feed conversion efficiency. The results showed that increasing concentrate feed dosage significantly affected broiler chicken body weight growth. The optimal dosage that produced the highest body weight gain was at 50%, indicating a balance between feed efficiency and growth. This study concluded that varying concentrate feed dosage significantly affected broiler chicken growth performance, and using the correct dosage can increase productivity and improve maintenance costs.